Neurophysiological Endophenotypes, CNS Disinhibition, and Risk for Alcohol Dependence and Related Disorders - Bernice Porjesz; Madhavi Rangaswamy (The Scientific World Journal)
Biological endophenotypes are more proximal to gene function than psychiatric diagnosis, providing a powerful strategy in searching for genes in psychiatric disorders. These intermediate phenotypes identify both affected and unaffected members of an affected family, including offspring at risk, providing a more direct connection with underlying biological vulnerability. The Collaborative Study on the Genetics of Alcoholism (COGA) has employed heritable neurophysiological features (i.e., brain oscillations) as endophenotypes, making it possible to identify susceptibility genes that may be difficult to detect with diagnosis alone. We found significant linkage and association between brain oscillations and genes involved with inhibitory neural networks (e.g., GABRA2, CHRM2), including frontal networks that are deficient in individuals with alcohol dependence, impulsivity, and related disinhibitory disorders. We reported significant linkage and linkage disequilibrium for the beta frequency of the EEG and GABRA2, a GABAA receptor gene on chromosome 4, which we found is also associated with diagnosis of alcohol dependence and related disorders. More recently, we found significant linkage and association with GABRA2 and interhemispheric theta coherence. We also reported significant linkage and linkage disequilibrium between the theta and delta event-related oscillations underlying P3 to target stimuli and GABRA2, a cholinergic muscarinic receptor gene on chromosome 7, which we found is also associated with diagnosis of alcohol dependence and related disorders. Thus, the identification of genes important for the expression of the endophenotypes (brain oscillations) helps when identifying genes that increase the susceptibility for risk of alcohol dependence and related disorders. These findings underscore the utility of quantitative neurophysiological endophenotypes in the study of the genetics of complex disorders. We will present our recent genetic findings related to brain oscillations and Central Nervous System (CNS) disinhibition.